Nanotube superfiber materials : science, manufacturing, commercialization - Schulz, Mark J.; Shanov, Vesselin N.; Yin, Zhangzhang; Cahay, M. (Micro & nano technologies., 2019)
Nanotube Superfiber Materials: Science, Manufacturing, Commercialization, Second Edition, helps engineers and entrepreneurs understand the science behind the unique properties of nanotube fiber materials, how to efficiency and safely produce them, and how to transition them into commercial products. Each chapter gives an account of the basic science, manufacturing, properties and commercial potential of a specific nanotube material form and its application. New discoveries and technologies are explained, along with experiences in handing-off the improved materials to industry. This book spans nano-science, nano-manufacturing, and the commercialization of nanotube superfiber materials. As such, it opens up the vast commercial potential of nanotube superfiber materials. Applications for nanotube superfiber materials cut across most of the fields of engineering, including spacecraft, automobiles, drones, hyperloop tracks, water and air filters, infrastructure, wind energy, composites, and medicine where nanotube materials enable development of tiny machines that can work inside our bodies to diagnose and treat disease.